Ritual ceremonial life: song text and spirit manifestation among the Zezuru People of Hwedza, Zimbabwe - Chikomo, Elijah (College of Music, 2025)
Ethnomusicologists, and scholars from adjacent fields, have examined and viewed music and spirituality from various perspectives. Studies have been successful in examining the function of music in worship in many cultures. The Zezuru people are a Zimbabwean Shona subethnic group and they practise bira rematendo, (a ritual ceremony) in which songs are performed to pacify ancestral spirits. This thesis examines how song text fosters spirit manifestation in a Zezuru bira rematendo ceremonial performance. I further report on the origin of songs performed at bira rematendo ritual ceremonies for the purpose of creating a conducive environment for spirit manifestation. Three theoretical frameworks guide the research, these are historicism, multispecies ethnography, and communication models. Guided by the three theories, and employing ethnographic methods of participant observation, face-to-face interviews and video recordings, the following are interrogated: the Zezuru religious life, the significance and role of the song textual meanings in linking the living and the living-dead. The study demonstrates how song texts bring out song meanings which communicate with ancestors while enabling manifestation of ancestral and alien spirits in the context of Zezuru bira ritual performance. Furthermore, the study illustrates the resultant physical behavioural change of practitioners during song performance in the bira rematendo event.